Bibliometrics to assess the productivity and impact of medical research - Ndwandwe, M.; Bishop, D. G.; Wise, R.; Rodseth, Reitze (South African Journal of Higher Education, 2021)
Background: Bibliometrics is the use of statistical and mathematical analysis to assess research production and quality. These metrics provide important insights into the quality and impact of research by applying standardised metrics. However, there are inherent limitations in their application. Objective: We aimed to review existing bibliometric indices and assess their comparative utility in the assessment of medical researchers. We specifically aimed to evaluate the utility of the h-index in identifying young or developing medical researchers with future research potential. Method: We conducted a focussed literature review on commonly used bibliometrics. To explore the utility of these metrics we then used them to evaluate a sample of researchers from a South African medical school faculty. Researchers were ranked with the following metrics: number of publications; h-index; citations per paper; citations per paper per year; and m-index. The h-index, citations and publication counts were drawn from ResearchGate and, if not available, from Google Scholar. The top 20 researchers, based on publication count, were then analysed further. Results: We identified 145 researchers for analysis of which 37 were excluded due to an inability to obtain additional information. Higher time-dependent metrics (publication count, citation count, h-index) were directly proportional to years since first publication. Indices that corrected for time, such as the m-index, provided more insight and better discrimination in identifying younger researchers with greater research potential. Conclusion: Bibliometrics have utility as part of the assessment of academic output but may be subject to time-dependent bias. Research quality is best measured using the h-index, g-index and m-index. The h-index is limited by being time dependent and field specific and overlooks highly cited papers. Bibliometrics that account for time, such as the m-index, should be considered in the early identification of young researchers, ideally accompanied by critical peer review.